Central African Republic : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Central African Republic's Request for Disbursement Under the Rapid Credit Facility. The implementation of the policies and structural reforms to which the authorities committed under the Extended Credit Facility (ECF) arrangement adopted in December remains key to ensuring macroeconomic stability and debt sustainability and restoring sustained inclusive growth. Additional external support, preferably in the form of grants, is also urgently required to meet C.A.R.'s elevated financing needs and ease the financial burden of the pandemic. These are also essential to the authorities' efforts to restore peace and prosperity in the country. The authorities intend to allow the fiscal deficit to increase to accommodate most of the fiscal impact of the pandemic, which will comprise a significant shortfall in revenue and additional outlays as part of the response plan. While they intend to streamline nonpriority expenditures, this accommodative stance will allow them to continue meeting pressing social, infrastructure, and security spending needs. The authorities have also reiterated their intention to pursue the policies and structural reforms to which they committed under the ECF arrangement approved last December.